LITERATUR REVIEW: RELEVANSI PENERAPAN KURIKULUM MERDEKA DENGAN KONSEP PEMIKIRAN KI HAJAR DEWANTARA - Alfiani Dyah Pratiwi; Slamet Slamet; Alfiani Dyah Pratiwi (Universitas Negeri Malang, 2024)
The independent curriculum is an educational policy that is currently being implemented. The independent curriculum in its implementation refers to the concept of liberating students. The independent curriculum is a program policy in the education sector that emphasizes giving freedom to schools to innovate in designing learning according to the needs and characteristics of students. Freedom to learn, character education, and differentiated learning are among the innovations in implementing the independent curriculum. Ki Hajar Dewantara's concept of thought is the basis for determining the education system in Indonesia. The background of this research is to review the literature to determine the relevance of implementing the independent curriculum with the thought concept of Ki Hajar Dewantara. The type of research used in this research is the literature study research method. The object of this research is an article regarding the implementation of the independent curriculum and its relevance to Ki Hajar Dewantara's thought concept. The results of the analysis show that there is relevance in implementing the independent curriculum with the concept of Ki Hajar Dewantara's thinking, such as the relevance of differentiated learning with the pedagogical vision put forward by Ki Hajar Dewantara in realizing Freedom of Learning. Apart from that, its relevance lies in the character of education which aims to view education not only as an educational initiative but also as a social system, which is in line with Ki Hajar Dewantara's educational philosophy in Taman Siswa.